Influence of exogenous NAA in Calophyllum inophyllum micro-environment seeds germination - Asri Insiana Putri; Liliek Haryjanto; Noor Khomsah Kartikawati; Arif Nirsatmanto; Sri Sunarti; Toni Herawan; Fajar Lestari; Anto Rimbawanto (Indonesian Journal of Applied Environmental Studies, 2022)
Throughout Indonesia, more than a hundred million ha of degraded forest and lands are still to be rehabilitated. High-quality tree seedlings are a key component of landscape restoration. The limited supply of quality seeds has been an obstacle so far. C. inophyllum is a tropical tree species that grow well under harsh environmental conditions. It can be used as an alternative tree species for degraded land rehabilitation. We present an efficient and reproducible protocol for improving seed quality with exogenous NAA hormones. The Murashige and Skoog (MS) medium was supplemented with NAA hormones (0 mg/l, 1 mg/l, 2 mg/l, and 3 mg/l of NAA) for observation of the influence of the exogenous NAA on seeds germination in micro-environment controlled. After seven weeks of incubation in axenic culture, the highest concentration of NAA (3 mg/l) showed the fastest average seed-breaking time of C. inophyllum (2.0 weeks), After three weeks, the roots were nearly five times longer (4.9 ± 0.1 cm) than the control (1.1± 0.1 cm), and the shoots were nearly three times longer (4.9 ± 0.1 cm) than the control (1.1± 0.1 cm). This research needs to be tested on a larger scale of cultivation.Di seluruh Indonesia, lebih dari seratus juta ha hutan dan lahan terdegradasi masih harus direhabilitasi. Bibit pohon berkualitas tinggi adalah komponen kunci dari restorasi lanskap. Terbatasnya pasokan benih berkualitas menjadi kendala selama ini. C. inophyllum adalah spesies pohon tropis yang tumbuh dengan baik di bawah kondisi lingkungan yang keras. Ini dapat digunakan sebagai jenis pohon alternatif untuk rehabilitasi lahan terdegradasi. Kami menyajikan protokol yang efisien dan dapat direproduksi untuk meningkatkan kualitas benih dengan hormon NAA eksogen. Media Murashige dan Skoog (MS) dilengkapi dengan hormon NAA (0 mg/l, 1 mg/l, 2 mg/l, dan 3 mg/l NAA) untuk pengamatan pengaruh NAA eksogen terhadap perkecambahan biji di lingkungan mikro dikendalikan. Setelah tujuh minggu inkubasi dalam kultur axenic, konsentrasi NAA tertinggi (3 mg/l) menunjukkan rata-rata waktu pemecahan benih tercepat C. inophyllum (2,0 minggu), Setelah tiga minggu, akar hampir lima kali lebih panjang (4,9 ± 0,1 cm) dari kontrol (1,1± 0,1 cm), dan tunas hampir tiga kali lebih panjang (4,9 ± 0,1 cm) dari kontrol (1,1± 0,1 cm). Penelitian ini perlu diuji pada skala budidaya yang lebih besar.